Perbedaan Fear Of Missing Out (Fomo) Pada Mahasiswa Dan Mahasiswi Di Fakultas Ushuluddin Adab Dan Dakwah Uin Mahmud Yunus Batusangkar - Pratama Putra, Rinaldi; Desmita, Desmita (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem in this research is the problem of Fear of Missing Out (FoMO) on social media sothat feelings of fear, worry, and anxiety arise when something interesting is left behind, causing a person to┬áfeel like he has missed an important event/event. The purpose of this study was to determine whether therewere differences in FoMO between students and female students at the Faculty of Ushuluddin Adab andDa'wah UIN Mahmud Yunus Batusangkar.The type of research used is aquantitative type of different test. The population in this study were1,039 students of the Faculty of Ushuluddin Adab and Da'wah of UIN Mahmud Yunus Batusangkar. The typeof sampling in this study was proportional sampling with a total error of 5%, so the number of samples in this┬ástudy were 290 people. The data collection technique used was a Likert Scale by distributing it to students at┬áthe Ushuluddin Adab and Da'wah Faculty. Data processing was carried out statistically with the help of SPSS┬áwindows version 20.The results of this study indicate that there is no significant┬á difference in FoMO among students at the┬áFaculty of Ushuluddin Adab and Da'wah UIN Mahmud Yunus Batusangkar. From the data obtained asignificance value (2-tailed) 0.0871 > 0.05, which means that there is no significant difference, which means┬áthat the hypothesis in this study (Ha) is rejected and (Ho) is accepted. With this the researchers obtained theresult that there were no significant differences in students and female students at the Faculty of Ushuluddin┬áAdab and Da'wah UIN Mahmud Yunus Batusangkar.Keywords: FoMO, Student, Student